2015
DOI: 10.1186/s12889-015-1491-1
|View full text |Cite
|
Sign up to set email alerts
|

Food habits, physical activities and sedentary lifestyles of eutrophic and obese school children: a case–control study

Abstract: BackgroundCivilization has produced lifestyle changes; currently, people ingest more calories than are expended, resulting in obesity. This study assessed the association between dietary habits, physical activities, and sedentary behaviors and the risk of obesity in schoolchildren in Mexico City.MethodsOf 1,441 children (6–12 years old) screened in elementary schools, 202 obese (BMI ≥95th pc) and 200 normal-weight children (BMI 25th- 75th pc), as defined by the 2000 CDC criteria, were included in a case–contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 20 publications
5
41
0
5
Order By: Relevance
“…A sedentary lifestyle is also a key risk factor for childhood obesity [5]. The present study demonstrated that participants who engaged in >60 min of television, video games, or computer usage were more prone to abnormal BMIs than those who did not engage in excessive television, video games, and computer usage.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A sedentary lifestyle is also a key risk factor for childhood obesity [5]. The present study demonstrated that participants who engaged in >60 min of television, video games, or computer usage were more prone to abnormal BMIs than those who did not engage in excessive television, video games, and computer usage.…”
Section: Discussionmentioning
confidence: 49%
“…Globally, an increased intake of energy-dense foods high in sugar and fat, and an increase in physical inactivity stemming from children’s obsession with electronic products (televisions, computers, and mobile phones) have been observed [1,5]. Studies have demonstrated that the BMI of school children is related to their physical activity levels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Poor eating habits and low levels of physical activity were associated with the risk of obesity. An obesogenic environment could be eliminated if teachers and parents worked together to instill healthy eating and physical activity habits [14].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the study respondents were women, reported purchasing packaged foods, and recognized the relevance of the information provided by nutrition labeling, which indicates that scientific information can be translated to a form that strengthens the ability of students to choose healthy foods [24]. …”
Section: Discussionmentioning
confidence: 99%